2014
DOI: 10.1111/1471-0528.12877
|View full text |Cite
|
Sign up to set email alerts
|

Brief sexuality communication—a behavioural intervention to advance sexually transmitted infection/HIVprevention: a systematic review

Abstract: Background Throughout the last decade substantial research has been undertaken to develop evidence-based behaviour change interventions for sexual health promotion. Primary care could provide an opportunistic entry for brief sexual health communication.Objectives We conducted a systematic review to explore opportunistic sexual and reproductive health services for sexual health communication delivered at primary health care level. Search strategyWe searched for studies on PubMed, ProQuest, CINAHL, Jstor, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Interventions focused on improving clinician–adolescent sexual risk communication are efficacious in preventing and reducing condomless sex (Cooper, Toskin, Kulier, Allen, & Hawkes, 2014). However, less is known with respect to drug use—a behavior that parallels sexual risk behaviors—and thus, the need to examine interventions targeting multiple adolescent HIV/STI risk behaviors remains.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions focused on improving clinician–adolescent sexual risk communication are efficacious in preventing and reducing condomless sex (Cooper, Toskin, Kulier, Allen, & Hawkes, 2014). However, less is known with respect to drug use—a behavior that parallels sexual risk behaviors—and thus, the need to examine interventions targeting multiple adolescent HIV/STI risk behaviors remains.…”
Section: Discussionmentioning
confidence: 99%
“…The review found evidence that BSC has some effect in the reduction and prevention of STIs/HIV infection. 40 There is, however, a lack of strong evidence to answer questions about the impact of BSC on improving sexual wellbeing other than the reduction and prevention of STIs/HIV. The review found only one paper designed to address the question of whether BSC improves sexual wellbeing.…”
Section: Development Of the Guideline For Brief Sexuality-related Commentioning
confidence: 99%
“…The review found only one paper designed to address the question of whether BSC improves sexual wellbeing. 40 This may reflect a lack of conceptual and methodological clarity in defining and measuring such an outcome. One study among adolescents found BSC to be helpful in increasing conversations around self-esteem and self-regulation, but the long-term sexual health outcomes of these conversations have not been documented.…”
Section: Development Of the Guideline For Brief Sexuality-related Commentioning
confidence: 99%
See 1 more Smart Citation
“…A review of clinical trials in the field of sexual health shows that most interventions have been made to reduce and prevent the transmission of sexually transmitted diseases (STD) and AIDS. It seems that there has not been a study of behavioral changes around sexual issues that affect one's self-esteem (7) and this necessitates further investigation in this regard.…”
Section: Introductionmentioning
confidence: 99%